A Letter from I.B. Gentleman: Sir Thomas Smith's Ulster scheme and its Scottish context. Issue 2 (2nd September 2017) - McMillan, Christopher
Abstract: Sir Thomas Smith (1513–1577) was a political philosopher and writer. His works Discourse of the Commonweal of This Realm of England (1549) and De Republica Anglorum (1562–65) are significant texts in early English political theory. Smith was also a colonizer and in 1572 embarked on a plantation scheme in Ulster. That year Smith's son published a pamphlet advertising the scheme to potential investors and adventurers. Smith claimed that participants "would form an aristocratic elite" (Ellis 266), but first had to drive out the "wicked barbarous and uncivil people, some Scottish and some wild Irish" (Strype 131). The pamphlet: A Letter from I. B. Gentleman, was both controversial and influential, and described as "the first printed publicity for an English colonial project" (Quinn 551). Though I. B. Gentleman is much studied, the Gaelic Scottish influence on Smith's plans, pamphlet and associated material has been insufficiently considered. This study seeks to address that deficiency.